(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the role of family, community, and society in raising young people in Uzbekistan. The issue of improving social and pedagogical cooperation between educational institutions was studied in a comparative and analytical manner with the experience of foreign countries , and the results of a comparative study of the scientific and research work of our scientists who have made a significant contribution to the education and upbringing of young people in the Republic of Uzbekistan, the development of their spiritual and moral qualities were reflected. Family, community and Ways to improve social and pedagogical cooperation between educational institutions, the results of experiments and tests conducted , the results of organized seminars and trainings, proposals, recommendations and conclusions are described in detail.